Reversal of anticoagulants: an overview of current developments - Greinacher, Andreas; Thiele, Thomas; Selleng, Kathleen (Thrombosis and Haemostasis, 2015)
Several new anticoagulants have entered the clinical arena or are under clinical development. These drugs include indirect (fondaparinux) and direct oral factor Xa inhibitors (rivaroxaban, apixaban, edoxaban, betrixaban), and the direct thrombin inhibitor dabigatran. Especially the oral direct FXa and FIIa inhibitors overcome many of the shortcomings of heparins and vitamin K antagonists (VKAs). They are administered orally at a fixed dose; regular monitoring is not necessary; interaction with other drugs or nutrition occur less than with VKAs and they are at least as effective as VKAs for most indications tested. They are associated with about 50 % less intracranial bleeding than VKAs. Nevertheless, they are still associated with bleeding complications. Bleeding can occur spontaneously or as a result of trauma or urgent surgery. In such situations rapid reversal of the anticoagulant effect is highly desirable. For unfractionated heparin protamine, and for VKAs prothrombin complex concentrates are available as specific antidotes. Under clinical development are: for the direct and indirect FXa inhibitors a modified recombinant FXa (andexanet alpha), which lacks enzymatic activity; and for dabigatran a Fab fragment of a monoclonal antibody (idarucizumab). In addition a small molecule (aripazine) has entered phase I clinical trials, which seems to inhibit nearly all anticoagulants but VKAs and argatroban. This review summarises the current options and strategies in development to antagonise anticoagulants with a focus on the status of the development of antidotes for the oral direct FXa and FIIa inhibitors.
Keywords: New anticoagulants; antidotes; apixaban; dabigatran; rivaroxaban